Etničnost, integracija in civilna družba - Vrečer, Natalija (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2004)
The research paper focuses mainly on the group of people that was forcibly displaced during the war in Bosnia-Herzegovina and sought exile in Slovenia. The author will try to answer the question to what extent do the Slovenian authorities allow the integration of forced migrants from Bosnia-Herzegovina into Slovenia. Further research question will address the role of ethnic factor in the integration processes, the causes for persistence of ethnicity, and the role of civil society in the integration processes of forced migrants.It will be argued in the research paper that the integration measures for forced and economic migrants contribute significantly to the social cohesion of the society on the whole, as they also integrate those migrants that lived in a given society before the arrival of newcoming groups.The methodology applied combines ethnographic research with comparative analysis.
Keywords: Slovenia; Slovenija; tujci; priseljenci; begunci; Bosna in Hercegovina; Bosnia and Herzegovina; narodna identiteta; kulturna identiteta; asimilacija; assimilation; integracija; civil society; civilna družba